2012
DOI: 10.1161/circimaging.112.973206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hemodynamics on Global and Regional Lung Perfusion

Abstract: Background-Cardiac hemodynamics affect pulmonary vascular pressure and flow, but little is known of the effects of hemodynamics on lung perfusion at the tissue level. We sought to investigate the relationship between hemodynamic abnormalities in patients with left heart failure and global and regional lung perfusion using lung perfusion quantification by magnetic resonance imaging. Methods and Results-Lung perfusion was quantified in 10 normal subjects and 28 patients undergoing clinically indicated left and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Whether due to LVSD37, 38 or IPF,39, 40, 41 pulmonary hypertension is associated with significantly increased morbidity and mortality. In addition to the postulated role of pulmonary hypertension, there is evidence demonstrating extensive redistribution of pulmonary blood flow in individuals with hemodynamically significant LVSD, underscoring a complex heart–lung interaction 42. Fundamentally, it is the intricate interplay of the heart and lung function that determines clinical outcomes among patients with LVSD.…”
Section: Discussionmentioning
confidence: 99%
“…Whether due to LVSD37, 38 or IPF,39, 40, 41 pulmonary hypertension is associated with significantly increased morbidity and mortality. In addition to the postulated role of pulmonary hypertension, there is evidence demonstrating extensive redistribution of pulmonary blood flow in individuals with hemodynamically significant LVSD, underscoring a complex heart–lung interaction 42. Fundamentally, it is the intricate interplay of the heart and lung function that determines clinical outcomes among patients with LVSD.…”
Section: Discussionmentioning
confidence: 99%
“…To explain this phenomenon, they suggested an increased pulmonary vasoconstriction due to an increased pressure in the pulmonary vasculature with sympathetic activation, eventually leading to no significant changes in pulmonary blood volume. Cao et al, 9 using MRI in a more recent study, found a decrease in Full paper: Dual-energy CT pulmonary angiography in pulmonary venous congestion BJR global pulmonary perfusion with decreasing cardiac index and underlined the complexity of cardiopulmonary interactions in determining pulmonary haemodynamics in left heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is reassuring that Cao et al 8 found that the perfusion of the lungs is directly related to the cardiac output. More importantly, they examined the relative perfusion of lungs in the supine position.…”
Section: Article See P 693mentioning
confidence: 97%
“…In addition, in HF, an expansion and central redistribution of blood volume from the periphery with prolonged time in the supine position results in paroxysmal nocturnal dyspnea and contributes to central sleep apnea. 12 In this regard, studies using the technique of Cao et al 8 comparing the gravitational distribution of flow after a prolonged period in the supine position will also be valuable. There may also be shifts in the distribution of blood volume and alteration of the distribution of pulmonary perfusion during exercise.…”
Section: Circ Cardiovasc Imagingmentioning
confidence: 99%
See 1 more Smart Citation